Biological Activities and Annotation of Bioactive Principle by Mass Spectrometry in the Root Extract of Boerhavia diffusa - Bhattarai, Keshav; Pandey, Indira; Sharma, Khaga Raj (Journal of Institute of Science and Technology, 2024)
Boerhavia diffusa is a well-known plant for ethnomedical uses. The plant is well known for its antioxidant and antidiabetic properties. Therefore, in addition to the antioxidant and antidiabetic properties of this plant, the present study focuses on exploring antibacterial properties, and metabolites present in Boerhavia diffusa. The preliminary phytochemistry was studied by the colour differentiation method. The phenolic and flavonoid content of the plant extracts was calculated using the Folin-Ciocalteu phenol and aluminum chloride colorimetry methods. Similarly, to find out the radical scavenging capacity of the available samples, one of the reliable methods (DPPH assay) was conducted. To evaluate the antidiabetic property, α-amylase and α-glucosidase inhibition were conducted by colorimetry methods. Results of phytochemical screening indicate that the plant is rich in metabolites including alkaloids, flavonoids, and terpenoids. Along with this, root extracts were found to be rich in total phenolic and flavonoid content with calculated values of 40.84±1.90 mg GAE/g and 37.01±1.61 mg QE/g, respectively. Similarly, among three methanolic extracts of root, stem, and leaf; the root showed the highest antioxidant activity with IC50 value 152.83±4.85 µg/mL. Among different solvent fractions of the stem of the same plant, the most potential antioxidant activity was shown by ethyl acetate fractions with an IC50 value of 82.96 ± 2.23 µg/mL. Additionally, no extracts and fractions were significantly active against α-amylase and α-glucosidase inhibition except ethyl acetate fraction. This fraction exhibited the enzyme inhibition property with IC50 value of 493.91±2.53 µg/mL for α-amylase and 96.31±10.65 µg/mL for α-glucosidase. To identify the chemical composition, mass spectrometry-based isolation and molecular annotation were carried out and metabolites like 3,9,10-trimethoxy-13-methyl-5,6-dihydroisoquinoline[2,1-b]isoquinolin-7-ium-2-olate, (E)-3-(4-hydroxy-3-methoxyphenyl)-N-[2-(4-hydroxyphenyl)ethyl]prop-2-enamide, 11,12-dihydro-2,3-(methylenedioxy)-7,8-dimethoxybenzo[c]phenanthridine, and (E)-3-(4-hydroxy-3-methoxyphenyl)-N-[2-(4-hydroxy-3-methoxyphenyl)ethyl]prop-2-enamide were reported. These results provide strong support for the ethnomedical uses of Boerhavia diffusa since the ancient period against diabetes and to cure infections. However, the evaluation of biological activities from the active compounds is not performed in this study.